Feasibility analysis of solar photovoltaic-wind hybrid energy system for household applications. (September 2020) - Al-Turjman, Fadi; Qadir, Zakria; Abujubbeh, Mohammad; Batunlu, Canras
Abstract: The significance of renewable energy resources provide a great opportunity to meet a single household electricity demand in Northern Cyprus. Purposefully, a 6 kW PV-Wind hybrid system seems to offer significant economic savings relative to the conventional grid system. Therefore, the main intention is to shed light on the technical as well as economic feasibility of combining renewable sources. The solar irradiance and wind speed data are analyzed for four populous cities of TRNC using RET-Screen software. The expected energy consumption for a normal household in Northern Cyprus comes out to be 11.27 kWh/d using HOMER software. The proposed hybrid model integrated with Ni-MH battery is designed in MATLAB software to visualize the possible energy output to be feed to the load. The results show that the proposed model provides alternative incentives to the consumers and it is economically feasible.